Severe hypoalbuminemia complicating a successful atrial switch operation (Senning) with cardiopulmonary bypass - report on a rare case - Datt, Vishnu; Datt, Diksha; Agarwal, Vijay; Yadav, Bharti; Vachhani, Parth (International Surgery Journal, 2024)
Post-operative hypoalbuminemia has been reported in 12% of neonates and 20% of infants; 97% occurs in the first 48 hours in neonates and infants undergoing cardiac surgery with cardiopulmonary bypass (CPB). Perioperative hypoalbuminemia is not independently associated with any post-operative morbidity. However, when analysed as a continuous variable, lower serum albumin levels have been reported to be associated with increased post-operative morbidity. Pre-operative low serum albumin level is independently associated with increased odds of post-operative hypoalbuminemia, and prolonged length of hospital stay. Immediate post-CPB (0-24 hour), lower serum albumin level is independently associated with an increased duration of mechanical ventilation. There is a relative paucity of literature on the impact of hypoalbuminemia in the paediatric population. Hypoalbuminemia is a marker of poor outcome in critically ill children and those undergoing a wide range of medical interventions. Albumin infusions may be an effective therapy for fluid resuscitation and for patients with severe hypoalbuminemia. We present a successful perioperative management of a 3 months old-male child, weighing 3.5 kg with dextro-transposition of great arteries (D-TGA) with regressed LV undergoing an atrial switch (Senning) procedure, and uneventful intraoperative course i.e. easy weaning from CPB. However, in the ICU, the baby suffered an unusual complication as severe hypoproteinaemia resulting in acute kidney injury (AKI) with complete anuria, generalized anasarca, hypotension requiring inotropes and vasopressors, and difficult weaning from ventilator.